Long COVID and Visual Signs and Symptoms. - Strawn, Lauren; Rutner, Daniella (Optometry & Visual Performance, 2024)
Background: Long COVID is a well-documented multi-system complication of COVID-19 infection. While exact mechanisms are unknown, several suggestions of possible pathogenesis have been proposed. Some of the symptoms experienced in long COVID are neurological in nature with visual function manifestations. Identifying these common visual symptoms in patients with long COVID can direct treatment and accelerate patients' recovery. Methods: A retrospective analysis on 47 patients who presented to the Neuro-Optometric Rehabilitation clinic at the SUNY College of Optometry University Eye Center between March 15, 2020 and December 31, 2022 was performed on those who self-reported a COVID-19 diagnosis. Medical records were reviewed for visual symptoms that included brain fog and fatigue, light sensitivity, headaches, eyestrain, diplopia, vestibular-related symptoms, and visual snow symptoms. A review of the patients' post-evaluation visual diagnoses, binocular, oculomotor, and/or accommodative dysfunction were noted and correlated to their presenting symptoms. Results: The most commonly reported symptom was vestibular-related (77%) for all patients, regardless of final diagnosis. Brain fog and fatigue (51%), light sensitivity (66%), headaches (66%), and eyestrain (66%) were also reported in the majority of patients. Multiple symptoms were reported in 91% of patients. Binocular dysfunction was the most common diagnosis (92% of patients), and many had multiple diagnoses (57%). Of note, 40% of patients self-reported a history of concussion. Conclusion: Patients with long COVID present with a variety of symptoms and often have multiple visual diagnoses. Thorough examination of visual skills is essential for this patient population, with special consideration of their vestibular function. Patients with long COVID have symptoms and visual signs that are similar to patients with post-traumatic vision disorder. As such, neuro-optometric rehabilitation commonly implemented as a mode of treatment for patients with concussion may be helpful in patients with long COVID.